2012
DOI: 10.1002/14651858.cd008411.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Sweet-tasting solutions for needle-related procedural pain in infants one month to one year of age

Abstract: Sweet-tasting solutions for needle-related procedural pain in infants one month to one year of age (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 95 publications
1
30
0
3
Order By: Relevance
“…Nonpharmacologic methods that are commonly used to reduce the effects of invasive procedures in newborns include breastfeeding (Obeidat & Shuriquie, 2015;Pillai Ridell, et al, 2015;Harrison et al, 2016;Okan et al, 2010;Yilmaz & Arikan, 2011;Shah, Herbozo, Aliwalas, & Shah, 2012;Uga et al, 2008;Marín Gabriel et al, 2013;Aguilar Cordero, Mur Villar, García García, Rodríguez López, & Rizo Baeza, 2014), pacifiers (da Motta & da Cunha, 2015Yilmaz & Arikan, 2011), and sucrose and sweet solutions (Kassab, Anabrees, Harrison, Khriesat, & Chen, 2017;Kassab, Foster, Foureur, & Fowler, 2012;Pillai Riddell et al, 2015;Yilmaz & Arikan, 2011). Other alternatives include music therapy (Marofi, Nikobakht, Badiee, & Golchin, 2015); massage, touching, and positioning (Hartley, Miller, & Gephart, 2015); and nesting, kangaroo care, foetal positioning, and wrapping (Morrow et al, 2010;Prasopkittikun & Tilokskulchai, 2003;Okan et al, 2010;Obeidat & Shuriquie, 2015;Ali, McGrath, & Drendel, 2016;Cong, 2015;Shu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nonpharmacologic methods that are commonly used to reduce the effects of invasive procedures in newborns include breastfeeding (Obeidat & Shuriquie, 2015;Pillai Ridell, et al, 2015;Harrison et al, 2016;Okan et al, 2010;Yilmaz & Arikan, 2011;Shah, Herbozo, Aliwalas, & Shah, 2012;Uga et al, 2008;Marín Gabriel et al, 2013;Aguilar Cordero, Mur Villar, García García, Rodríguez López, & Rizo Baeza, 2014), pacifiers (da Motta & da Cunha, 2015Yilmaz & Arikan, 2011), and sucrose and sweet solutions (Kassab, Anabrees, Harrison, Khriesat, & Chen, 2017;Kassab, Foster, Foureur, & Fowler, 2012;Pillai Riddell et al, 2015;Yilmaz & Arikan, 2011). Other alternatives include music therapy (Marofi, Nikobakht, Badiee, & Golchin, 2015); massage, touching, and positioning (Hartley, Miller, & Gephart, 2015); and nesting, kangaroo care, foetal positioning, and wrapping (Morrow et al, 2010;Prasopkittikun & Tilokskulchai, 2003;Okan et al, 2010;Obeidat & Shuriquie, 2015;Ali, McGrath, & Drendel, 2016;Cong, 2015;Shu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Various doses were evaluated, and the optimal dosage will need to be determined in the future. A review on sweettasting solutions in venipuncture-related procedural pain in infants aged between 1 and 12 months concluded that evidence was insufficient to support effectiveness, despite results being promising [95]. In individual studies, duration of cry was significantly reduced in this population compared with water, and pain was found to be significantly reduced compared with the control group.…”
Section: Sucrosementioning
confidence: 97%
“…Les réactions positives envers la saveur sucrée se manifestent donc avant même que le nourrisson ait eu la possibilité d'ingérer du sucre et donc d'apprendre l'association entre son goût et son apport énergétique. La saveur sucrée (et non l'apport calorique associé) présente un effet analgésiant qui est mis en application en pédiatrie en présentant une solution très sucrée à un nouveau-né pour atténuer les douleurs ressenties lors d'interventions modé-rément douloureuses (piqûre par exemple) (pour une revue voir [38,40]). Il est intéressant de noter que l'organisme ne s'adapte pas à cet effet analgésiant : l'application de sucre répétée trois jours de suite produit le même effet [41].…”
Section: Développement De L'attraction Pour Le Sucreunclassified